1990
DOI: 10.1002/aic.690360212
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and parameterization of interfacial gas absorption

Abstract: Experiments of simultaneous absorption of carbon dioxide and helium, in transient absorption regimes, have been carried out in a gasliquid flume for stratified-type cocurrent flows. There was a need to improve a method of chromatographic analysis for helium and CO, titrations in the gaseous phase and the liquid phase; this led us to study simultaneous absorption of CO, and He independent of dynamic conditions. In addition the dominant wave characteristics were studied and the interfacial friction velocity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…(3) The Schmidt number is fairly well related with the masstransfer coefficient. This has been confirmed in studying simultaneously absorption of carbon dioxide and helium, two gases presenting a large contrast of molecular diffusivity (Caussade et al, 1990).…”
Section: Kl=kl (Us I D L~v L A)mentioning
confidence: 74%
See 3 more Smart Citations
“…(3) The Schmidt number is fairly well related with the masstransfer coefficient. This has been confirmed in studying simultaneously absorption of carbon dioxide and helium, two gases presenting a large contrast of molecular diffusivity (Caussade et al, 1990).…”
Section: Kl=kl (Us I D L~v L A)mentioning
confidence: 74%
“…(1) Most absorption models proposed that the mass-transfer coefficient varies with -1/2 exponent of the Schmidt number (Levich, 1962;Fortescue and Pearson, 1967;Davies, 1972;Ueda et al, 1977;Henstock and Hanratty, 1979). Recently, Jahne et al (1987) and Caussade et al (1990) showed that the Schmidt number exponent is equal to -1/2 for rather strong interfacial stress and a clean interface whereas it is equal to -2/3 when the interface resembles a wall.…”
Section: Kl=kl (Us I D L~v L A)mentioning
confidence: 99%
See 2 more Smart Citations
“…Ce coefficient a été étudié dans des configurations variées: écoulements de jets, écoulements de bulles, film tombant, cuves agitées, écoulements en canal (THEOFANOUS (1976)). Dans ces conditions, les modèles locaux d'absorption (AlSA et al (1981); CAUSSADE et al (1990)) expriment le coefficient de transfert k, en fonction des paramètres suivants:…”
Section: Expérimental Set-up For Absorption Experimentsunclassified